Psychosocial Factors in Workers of an Educational Organization and their Relationship with Psychic Exhaustion - Anaya-Velasco, Ana (2021)
Objective. To evaluate the psychosocial factors perceived by workers in a higher education public organization and their relationship with the psychic exhaustion. Method. Research was cross-sectional, 292 workers  participated and it was used a test battery to evaluate the dimensions: Work Context, Work Content and  individual Factors, as independent variables and Psychic Exhaustion as a dependent variable. Results.  Perception of the participants was favorable by more than 80%. Psychosocial dimensions indicated a medium, positive and statistically significant correlation with the Psychic Exhaustion, consistent with Odds Ratio analysis. Individual Factors was the dimension with the greatest influence according to the multiple  linear regression model, followed by Work Content.